Story Telling Method To Develop Speaking Skills Student In Narrative Text At SMP Negeri 5 Pematang Siantar - Rohdearni Wati Sipayung; Ridwin Purba; Mariami Sitompul (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2024)
The aim of this research was to find out the influence of the ability in mastering dialogue on students speaking comprehension at SMP Negeri 5 Pematang Siantar in the academic year of 2022/2023. This research was classified as a true-experimental study. It involved 64 students from two class, as the experimental class 32 students and as the control class 32 students. The experimental and control class was students taught using essay test form story Bawang Merah and Bawang Putih. The data were obtained by using pre-test and post-test. The data of the pre-test and post-test of both groups were analyzed by using descriptive and inferential statistic. (SPSS 26.0). The result of the research shows that the testing hypothesis of post-test score is 86,56, shows that tcount (0,970) > ttable (2,188) at the significance level a = 0.05 and degrees of freedom (df) = 11. H0 is rejected and Ha is accepted. So, it means that the influence of the ability in mastering dialogue is significant on students speaking comprehension at SMP Negeri 5 Pematang Siantar